2018
DOI: 10.1016/j.newast.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic variations with twice the accretion disk precession period in the old nova V603 Aquilae

Abstract: A dense series of long and high time resolution light curves of the old nova V603 Aql, covering 22 nights (19 of which are consecutive), are analyzed in order to identify and characterize variations on the time scale of hours and days. The well known 3.5 hour modulation, observed many times in the past and considered to be due to a long lasting, albeit not entirely stable superhump, is recovered at a period of 0.1453 days and an amplitude of ∼ 0 m . 062. Most interesting, however, is the detection of highly si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The only consistent modulation present in the light curve has a slightly variable period close to 3.5 h, about 6% longer than the orbital period. It has first been detected by Haefner (1981) and then be confirmed by many authors (see Bruch & Cook 2018). Additionally, Patterson et al (1998) observed a modulation with a period being about 3% less than the orbital period.…”
Section: Appendix B: System Parametersmentioning
confidence: 62%
“…The only consistent modulation present in the light curve has a slightly variable period close to 3.5 h, about 6% longer than the orbital period. It has first been detected by Haefner (1981) and then be confirmed by many authors (see Bruch & Cook 2018). Additionally, Patterson et al (1998) observed a modulation with a period being about 3% less than the orbital period.…”
Section: Appendix B: System Parametersmentioning
confidence: 62%
“…It is therefore an unsolved question why positive superhumps are also occasionally observed in systems with a much higher mass ratio and a wider orbit. Prominent examples are, among others, UU Aqr (Patterson et al 2005), V603 Aql (Bruch & Cook 2018, and references therein), KR Aur (Kozhevnikov 2007), TV Col (Rette, et al 2003), V751 Cyg (Patterson et al 2001;Papadaki et al 2009), V795 Her (Patterson & Skillman 1994;Papadaki et al 2006), and V378 Peg (Kozhevnikov 2012). TT Ari another case.…”
Section: Introductionmentioning
confidence: 99%